Pedagogical practice and professional training of mathematics teachers - Cibulskaitė, Nijolė; Bernotas, Vytautas (Lietuvos matematikos rinkinys, 2013)
The aim of this paper is to highlight the features of the improvement of student’s professional competencies in the final stage of the pedagogical studies in the Lithuanian University of Educational Sciences. 84 students of the fourth year studies of mathematics and computer science specialty were interviewed using questionnaire. The research methods: statistical quantitative analysis of empirical data; qualitative analysis of students’ reports of carried out teaching practice. The results revealed: the studies of mathematics didactics and teaching practice effectively helped students develop their professional competencies; the experience gained during the teaching practice determinated student’s choosing of teaching career mostly.
Keywords: prospective mathematics teacher; professional competencies; teaching practice